An Effect of Leadership and Work Motivation Employee Job Satisfaction at the Regional Tax and Level Management Agency North Medan - Masrayhani; Rindi Andika; Cahyo Pramono (Budapest International Research and Critics University, 2022)
This research was conducted to know the influence of leadership and motivation on employee job satisfaction at the regional tax and retribution management agency branch Medan Utara. This research approach uses an associative where this study aims to analyze the problem that there is a relationship between a variable and other variable. The population in this study were employees who worked in the office of the regional tax and retribution management agency branch Medan Utara. This study uses saturation or census techniques where all of the population was used as a sample, and the number of employees who work in the office of the regional tax and retribution management agency branch in North Medan is 70 people. The results of this study are that there is a significant influence between leadership on job satisfaction 0.000 <0.05, as well as between the motivation variable on job satisfaction, where there is a considerable influence. There is also a simultaneous research result known that Fount 227.107> F table 2.74 with a probability of sig 0.000 <0.05, it is stated that the hypothesis Ho (rejected) and Ha are accepted, indicating that there is an influence between leadership and motivation on employee job satisfaction. The coefficient of determination obtained is 0.890, which means 89%, where other factors influence the remaining 11%.